Cerebral Venous Sinus Stenting for the Treatment of Idiopathic Intracranial Hypertension in a Child - Rodrigues, Leonardo Henrique da Silva; Aguiar, Guilherme Brasileiro de; Torres, Hélio Henrique Jorge; Xander, Paulo Adolfo Wessel; Assunção, Fernanda Boldrini; Scoppetta, Thiago Luiz Pereira Donoso; Jory, Mauricio; Veiga, José Carlos Esteves; Conti, Mario Luiz Marques (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Idiopathic intracranial hypertension (IIH) is a disease characterized by an increase in the opening pressure of the cerebrospinal fluid (CSF) associated with symptoms of elevated intracranial pressure (ICP). The condition is more prevalent in women and typically managed clinically. Surgical treatment is reserved for select refractory cases. The well-established surgical procedures for the management of IIH are CSF shunting and fenestration of the optic nerve sheath. These procedures, however, are associated with high rates of complication and recurrence.More recently, venous sinus angioplasty with stents has been employed in cases with documented narrowing of the sigmoid-transverse sinuses. This technique is associated with a significant reduction in the venous pressure gradient at the stenosis site, alleviating the symptoms of intracranial hypertension.We report a case of a previously healthy 12-year-old patient who presented with 10-day history of headaches, blurring of vision, nausea and vomiting, which evolved with worsening of the visual acuity and papilledema. Imaging scans disclosed stenosis of the right transverse and sigmoid sinuses. The patient underwent stenting of the stenotic venous segments and showed good evolution, with significant clinical improvement within 24 hours of the procedure.
Keywords: intracranial hypertension; papilledema; pseudotumor cerebri; intracranial thrombosis; endovascular procedures